Safety of Intrcameral Moxifloxacin Ophthalmic Solution for Antibacterial Prophylaxis in Cataract Surgery - Raja Abrar, Rasheed Jaffri, Shahzad Iftikhar, Rabia Bashir, Zeba Matin, Badar ud Din Ather Naeem (Pakistan Journal of Ophthalmology, 2009)
Purpose: To evaluate the safety profile of intracameral moxifloxacinin 0.5% ophthalmic solution in terms of anterior chamber (AC) reaction and endothelial toxicity. Material and Methods: This prospective study was conducted in the department of Ophthalmology Fauji Foundation Hospital, Rawalpindi, from December 2006 to November 2007 and comprised of 200 patients. The patients were divided into two groups. Group 1 received 0.1 ml of intracameral moxifloxacin 0.5 % ophthalmic solution at the conclusion of the surgery and the patients in the group 2 were not given the intracameral antibiotic. None of the patients was given postoperative sub conjunctival antibiotic and steroid injection. All patients were examined for AC reaction and pachymetry was done preoperatively and postoperatively (first day, first week and 4 weeks postoperatively). Anterior chamber reaction and pachymetry values between the two groups were compared .Statistical analysis was done by using paired sample t test. P value of less than 0.05 was taken as significant. Results: There was no statistically significant difference in corneal oedema (measured by pachymetry) between the two groups on the first postoperative day (p=624), and one month postoperatively (p=0.186). Anterior chamber reaction on the 1st postoperative day was not different in both groups (p=0.610). At 4 weeks there was no reaction in any patients and corneal thickness was also restored to preoperative level. Conclusion: Intracameral moxiloxacin 0.5% ophthalmic solution seems to be safe in terms of AC reaction and endothelial toxicity.